Mediating role of resilience on burnout to well-being for hospital nursing staff in Northeast China: a cross-sectional study - Jin Zhao; Wei Tian; Xin Meng; Xiujie Zhang; Tieying Shi; Xu Tang; Lihong Jia (BMJ Open)
Objectives The well-being of nursing staff is closely related to nursing performance and patient safety. It has attracted much attention from nursing managers and researchers. However, the most important influencing factors and their relationships are not fully understood. The purpose of this study is to identify the factors influencing the well-being of nurses and find out the mediating role of resilience of from burnout to well-being of hospital nursing staff.Design A descriptive, multicentre cross-sectional study design.Settings 111 hospitals in Northeast China were randomly selected by the random cluster sampling method.Participants An online survey was administered to 11 827 nurses in December 2021, who engaged in clinical, nursing or management work and volunteered to participate.Outcomes measures The sociodemographic characteristics, general well-being schedule, Maslach burnout inventory and Connor–Davidson resilience scale were used to assess all participants.Results There are 15 variables entered into the regression equation, which can jointly predict 57.80% of the variance. There were a number of well-being-related factors identified. The individual factors include age, educational level, exercise, smoke, drinking, general health status, chronic disease, burnout and resilience. The organisational factors include psychological group, participating in psychological group activities, leadership training or communication training, working years, monthly income and night shifts. The results showed that the structural equation model of partial mediating effect of resilience was established. And the partial mediating effect accounted for 16.91% (−0.083/0.488) of the total effect.Conclusions There were a number of well-being-related factors identified, including individual and organisational factors, which provide directions for targeted support and interventions of nurses. It could improve the resilience of hospital nursing staff, reduce burnout and enhance well-being.